Got political skill?: The direct and moderating impact of political skill on stress, tension and outcomes in restaurants - Kim, Taegoo Terry; Karatepe, Osman M.; Chung, Ung Young (Emerald Group Publishing Ltd, 2019)
Purpose The purpose of this study is to propose a research model in which political skill (PS) exerts a direct effect on role stress, job tension, work engagement and service performance and buffers the deleterious impact of role stress on job tension. The model also investigates the interrelationships of role stress, job tension, work engagement and service performance. Design/methodology/approach The sample was drawn from 261 customer-contact employees in 15 casual restaurants in South Korea. Structural equation modeling was used to assess the aforementioned relationships. Findings The findings illustrate that PS alleviates role stress and job tension, while it fosters work engagement and service performance. PS is a panacea to the deleterious impact of role stress on job tension. As expected, role stress heightens job tension, while job tension mitigates work engagement. The findings further reveal that work engagement exerts a positive impact on service performance. Practical implications Training interventions can be used to develop employees' PS. Management should hire the individuals with high PS because such employees can work in harmony with the organizational culture and experience lower role stress and job tension. Originality/value The extant hospitality research implicitly demonstrates that very little is known about the outcomes of PS and its moderating role on the relationship between role stress and job tension. The current work set out to fill in this gap.
Keywords: Work engagement; Role stress; Service performance; Job tension; Political skill; Restaurant customer-contact employees